Penggunaan Makna Emotif pada Balasan Kolom Komentar Admin TikTok @pesonaindonesia - Helwa, Luthfia; Arif Bowo, Sigit (Widyantara, 2024)
The aim of this research is to describe the types of emotive meanings found in replies to @PesonaIndonesia's TikTok comments. This research uses qualitative research methods. The data source from this research is a response to admin comments on the tiktok account @PesonaIndonesia. The resulting data comes from replies to admin comments on the @PesonaIndonesia tiktok account which contains emotive meaning. After analysis, there were 104 data indicating emotive meanings which were divided into three types, including 22 data indicating high emotive meanings, 46 data indicating friendly emotive meanings, 36 data indicating harsh emotive meanings. The meaning of high emotive consists of the emotive wisdom, emotion, surprise, annoyance, cunning. The meaning of friendly emotive consists of fun, happy, proud, joyful and pitiful. The meaning of rough emotive consists of indifference, emotion, frustration, surprise and annoyance. The implications of the results of this research for learning Indonesian through Reply to admin comments @PesonaIndonesia are suitable for use as a learning medium for students which is useful for increasing knowledge and insight in the field of language. Apart from that, it is also a literacy medium in analyzing the meaning of words and sentences. Words or sentences that express various kinds of emotional expressions and forms can be used as lessons for students who want to know how to explain a meaning. The aim of this research is to describe the meaning of emotives contained in replies to @pesonaindonesia's TikTok comments. This research uses qualitative research methods. Data collection techniques in this research are through observation and documentation. Next, for data analysis techniques, use reading, listening and note-taking techniques, then use documentation by capturing screenshots of replies to admin comments that contain high emotive meaning, friendly emotive meaning and harsh emotive meaning. After analysis, there were 104 data showing emotive meanings which were divided into three types, including 22 data showing high emotive meanings, 46 data showing friendly emotive meanings, 36 data showing harsh emotive meanings. The meaning of high emotive consists of the emotive wise, emotional, surprised, irritated, cunning. The meaning of friendly emotive consists of fun, happy, proud, joyful and pitiful. The meaning of rough emotive consists of indifference, emotion, frustration, surprise and annoyance. The implications of the results of this research for learning Indonesian through replies to admin comments @pesonaindonesia are suitable for use as a learning medium for students which is useful for increasing knowledge and insight in the field of language.